La invisibilización de la comunidad lgbti de Latacunga en los programas radiofónicos de la ciudad. - Reinoso Sánchez, Amanda Gabriela (2018)
The main objetive of this project is the definition of the reason when there are not spaces to the participation of LGBTI collective members on Latacunga city radios at this programation contents and it was a radial proposal to obtain more visibility spaces, inclusion and promotion for LGBTI group rights in concordance to (LOC) Comunication Organic Law and the regulations of the radial spaces in private, public and community media. The porpouse offers some alternatives for local radios to strong the programs and contents by participation and including communication with this special community. The methodology was qualitative and applying explicative and description levels, enterview were applied for main producers of Latacunga 10 local radios; the focal group worked with members of LGBTI collective Silueta X and group of people who are identified with the community but they do not have direct relationship. In Latacunga respect of 10 local radios, 6 of them are private, 2 public and 2 communitarian, in any of them there are not productions by LGBTI community, or spaces for the collective participation. In another topic, some members of LGBTI community do not have participation in radiophonic programs in this city or other spaces by the scare to become victims of homophobic critics that can produce social violence, by this reason they have to find another mechanisms that can help them like foros, and other spaces that can help to promote their rights.